Between yesterday occupied and tomorrow "liberated". The consequences of the period 1940-1944 on the French police and police society - Berlière, Jean-Marc (Hispania Nova, 2021)
Although brief (1940-1944), the period of German occupation and Vichy government constitutes a decisive period for French police institution and society. State control, centralization and professionalization characterizing today the French police date back to this period, together with a dark recurrent image linked to the missions accomplished by the police, within the context of policies of exclusion and repression forced upon by Pétain government and collaboration established with Nazi occupiers.